A note on parallel algorithms for optimal h-v drawings of binary trees - Panagiotis T. Metaxas; Grammati E. Pantziou; Antonis Symvonis (Computational Geometry, 1998)
In this paper we present a method to obtain optimal h-v drawings in parallel. Based on parallel tree contraction, our method computes optimal (with respect to a class of cost functions of the enclosing rectangle) drawings in O(log2n) parallel time by using a polynomial number of EREW processors. The number of processors reduces substantially when we study minimum area drawings. Our work places the problem of obtaining optimal size h-v drawings in NC, presenting the first algorithm with polylogarithmic time complexity.